Metaplastic carcinoma of breast and neurofibromatosis 1: A rare association - Gnanapriya Vellaisamy; Suravi Mohanty; Pritilata Rout; Suraj Manjunath (Indian Journal of Medical and Paediatric Oncology)
Neurofibromatosis 1 (NF1) patients are generally at higher risk of developing common malignant tumors such as brain and soft tissue tumors. These patients are 5-fold increased the risk of developing breast cancer by the age of 50 years after that the risk remains the same. The most common reported cancer is infiltrating duct carcinoma. We report a case of 61-year-old female with NF1 presented with pain and breast lump for the past 2 months. On mammography, a retroareolar solid cystic lesion measuring 32 mm × 30 mm × 30 mm was noted which was definitive for malignancy. Right-modified radical mastectomy with axillary lymph node dissection was done which revealed a neoplasm composed of glandular and squamous components. Immunohistochemically, these cells were triple negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2-neu and expressed markers of basal cell differentiation. The final pathological staging was T2N0M0. This is the fourth case report in the English literature with such association. In this case report, we discussed the importance of breast cancer screening in such patients along with a review of the literature.